2013
DOI: 10.1186/1471-244x-13-284
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in people with severe and enduring anorexia nervosa: a comparison of generic and specific instruments

Abstract: BackgroundCriticisms that generic measures of health-related quality of life (HRQoL) are not sensitive to impairment in anorexia nervosa (AN) has spurred the development of disease-specific measures. This study aimed to compare the psychometric properties of a generic to a disease-specific measure of HRQoL.Methods63 participants with AN completed measures of a generic HRQoL (SF-12), disease-specific HRQoL (Eating Disorders Quality of Life Questionnaire; EDQOL), functional impairment (days out of role; DOR; Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Evidence for the reliability (α = 0.78–0.93) and validity of the SF-36 domains has been demonstrated in previous research (30, 31). Moreover, scores on an abbreviated version of the SF-36 (the SF-12) have been shown to predict changes in functional impairment and eating disorder severity over 12-month follow-up in patients with SE-AN (32). In the current study, we focused on three SF-36 domains with particular relevance to SE-AN: role limitations due to physical health problems (role-physical), social functioning, and emotional well-being.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the reliability (α = 0.78–0.93) and validity of the SF-36 domains has been demonstrated in previous research (30, 31). Moreover, scores on an abbreviated version of the SF-36 (the SF-12) have been shown to predict changes in functional impairment and eating disorder severity over 12-month follow-up in patients with SE-AN (32). In the current study, we focused on three SF-36 domains with particular relevance to SE-AN: role limitations due to physical health problems (role-physical), social functioning, and emotional well-being.…”
Section: Methodsmentioning
confidence: 99%
“…In general, a distinction can be made between studies focusing on Health-Related Quality of Life (HRQoL), in which satisfaction with life is considered in relation to physical and mental health, and studies focusing on QoL from a multidimensional perspective, based on the individual's personal perceptions, behaviors and circumstances (Schalock 2004). A large part of the existing QoL studies in the field of AN primarily focuses on HRQoL, which is being assessed using both generic and disease-specific instruments, such as the Medical Outcomes Study 36-Item Short Form (SF-36), the Health-Related Quality of Life in Eating Disorders Questionnaire (HErQoLED) and the Eating Disorders Quality of Life Questionnaire (EDQOL) (Engel et al 2009;Jenkins et al 2011;Mond et al 2005;Mitchison et al 2013). These studies however are subjected to a number of limitations.…”
Section: Introductionmentioning
confidence: 99%
“…It also provides partial support that generic measures of QoL perform well in ED samples (Mitchison et al, 2013; see also Ackard et al, 2014), although this was not a focus of the current study. However, the finding that substance use was positively associated with greater PCS scores (and no associations with social support) was unexpected and in contrast to the findings regarding mental health QoL.…”
Section: Discussionmentioning
confidence: 64%
“…Many studies have used generic measures of QoL, which have been criticized based on a possible lack of sensitivity to disorder-specific symptoms. However, in a study comparing generic and disease-specific measures of QoL in females with longstanding anorexia nervosa, Mitchison et al (2013) found that a generic measure of QoL (the SF-12; Ware et al, 1996) adequately predicted changes in functional impairment and ED pathology, although this was limited to a small subsample of individuals with EDs. One prominent measure of impairment in EDs (the Clinical Impairment Assessment questionnaire; CIA, specifically aims to address impairment as a result of ED symptoms.…”
mentioning
confidence: 96%